2016
DOI: 10.1016/j.mito.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial common deletion is elevated in blood of breast cancer patients mediated by oxidative stress

Abstract: The 4,977 bp common deletion is one of the most frequently observed mitochondrial DNA (mtDNA) mutations in human tissues and has been implicated in various human cancer types. It is generally believed that continuous generation of intracellular reactive oxygen species (ROS) during oxidative phosphorylation (OXPHOS) is a major underlying mechanism for generation of such mtDNA deletions while antioxidant systems, including Manganese superoxide dismutase (MnSOD), mitigating the deleterious effects of ROS. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…carried out a comprehensive experiment to detect the mtDNA 4977 as well as mtDNA copy number alteration in breast carcinoma and benign breast disease patients. 85 The authors revealed that the mtDNA 4977 in the blood of breast carcinoma patients was significantly higher (51/107, 48%) than that of benign breast disease patients and healthy controls. This deletion has also been found to be correlated with a lower mtDNA content and higher MnSOD level and oxidative damage in both group patients.…”
Section: Breast Cancermentioning
confidence: 97%
“…carried out a comprehensive experiment to detect the mtDNA 4977 as well as mtDNA copy number alteration in breast carcinoma and benign breast disease patients. 85 The authors revealed that the mtDNA 4977 in the blood of breast carcinoma patients was significantly higher (51/107, 48%) than that of benign breast disease patients and healthy controls. This deletion has also been found to be correlated with a lower mtDNA content and higher MnSOD level and oxidative damage in both group patients.…”
Section: Breast Cancermentioning
confidence: 97%
“…Damage to the mitochondrial genome also involves a 4977 base pair deletion, known as the “Common Deletion”, which occurs with high frequency in patients with mitochondrial diseases, and also in aged post-mitotic and quiescent cells including the RPE and neural retina ( Fig. 1 ; Barreau et al, 1996 ; Karunadharma et al, 2010 ; Nie et al, 2016 ; Huang et al, 2018 ). These results were confirmed in subsequent research, showing a biphasic increase in the ratio of this mutation in the retina.…”
Section: Rpe Mitochondria Damage and Dysfunction During Normal Agingmentioning
confidence: 99%
“…A recent sequencing study analyzed somatic mtDNA mutations in 1675 tumors, revealing 1907 mtDNA mutations [73]. The common 4977-bp mtDNA deletion has also been observed with a relatively high frequency in blood samples from breast cancer patients, strengthening the link between mtDNA mutation and cancer [74].…”
Section: Mitochondrial Dna In Common Diseasesmentioning
confidence: 99%